Pacific finance sector brief Tonga. (Pacific finance sector briefs., 2019)
The National Reserve Bank of Tonga (NRBT) is the countrys central bank and is responsible for the licensing, regulation, and supervision of financial institutions. The country has four licensed commercial banks, two of which are branches of international banks. While the finance sector is currently stable, it lacks diversity and is relatively underdeveloped. Regulatory vigilance is essential due to risks arising from lenient lending standards and a lack of supervision of the small number of nonbank financial institutions. To increase financial stability, the government is aiming to improve the NRBTs supervision, regulation, and legal framework.